Finalisation and validation of the rheumatoid arthritis impact of disease score, a patient-derived composite measure of impact of rheumatoid arthritis: a EULAR initiative. Issue 6 (2nd May 2011) - Gossec, L; Paternotte, S; Aanerud, G J; Balanescu, A; Boumpas, D T; Carmona, L; de Wit, M; Dijkmans, B A C; Dougados, M; Englbrecht, M; Gogus, F; Heiberg, T; et al.
Abstract : Objective: A patient-derived composite measure of the impact of rheumatoid arthritis (RA), the rheumatoid arthritis impact of disease (RAID) score, takes into account pain, functional capacity, fatigue, physical and emotional wellbeing, quality of sleep and coping. The objectives were to finalise the RAID and examine its psychometric properties. Methods: An international multicentre cross-sectional and longitudinal study of consecutive RA patients from 12 European countries was conducted to examine the psychometric properties of the different combinations of instruments that might be included within the RAID combinations scale (numeric rating scales (NRS) or various questionnaires). Construct validity was assessed cross-sectionally by Spearman correlation, reliability by intraclass correlation coefficient (ICC) in 50 stable patients, and sensitivity to change by standardised response means (SRM) in 88 patients whose treatment was intensified. Results: 570 patients (79% women, mean±SD age 56±13 years, disease duration 12.5±10.3 years, disease activity score (DAS28) 4.1±1.6) participated in the validation study. NRS questions performed as well as longer combinations of questionnaires: the final RAID score is composed of seven NRS questions. The final RAID correlated strongly with patient global (R=0.76) and significantly also with other outcomes (DAS28 R=0.69, short form 36 physical −0.59 and mental −0.55, p<0.0001 for all). Reliability was high (ICC 0.90; 95% CI 0.84 to 0.94) and sensitivity to change was good (SRM 0.98 (0.96 to 1.00) compared with DAS28 SRM 1.06 (1.01 to 1.11)). Conclusion: The RAID score is a patient-derived composite score assessing the seven most important domains of impact of RA. This score is now validated; sensitivity to change should be further examined in larger studies.